ANALISIS CAMPUR KODE DALAM DIALOG FILM KOMANG: KAJIAN SOSIOLINGUISTIK - Ni Putu Risna Putri; Ni Made Dhanawaty; I Gusti Ngurah Mayun Susandhika (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to identify and analyze the types of code-mixing and the factors that cause code-mixing in the dialogue of the film Komang. This study uses a descriptive qualitative approach with the free-involved-listening technique (SBLC), followed by note-taking to transcribe the data. The data were analyzed using the equivalent method (metode padan) to identify the types and causal factors of code-mixing. The results show that there are three types of code-mixing found in the dialogue of the film Komang, namely inner code-mixing, outer code-mixing, and mixed code-mixing. The factors underlying the occurrence of code-mixing include vocabulary limitation, language habits, specific terms or expressions, and social environment influence. This study shows that code-mixing in film dialogue reflects the diversity of cultural and linguistic backgrounds of the speakers, while enriching sociolinguistic studies on linguistic phenomena in Indonesian film media.